OUTCOME OF ENDOSCOPIC THERAPEUTIC INTERVENTIONS: ARE THEY DIFFERENT AMONG VARIOUS NON- MALIGNANT ESOPHAGEAL DISEASES - Khan, Rustam; Abid, Shahab; Hamid, Saeed; Abbas, Zaigham; Shah, Hasnain; Jafri, Wasim (Journal of Ayub Medical College Abbottabad, 2005)
Background: This study was carried out to evaluate and compare the outcome of various causes of non-malignant lesions of the esophagus after endoscopic therapeutic intervention. Methods: A cohort of patients with non-malignant dysphagia presenting at Aga Khan University hospital, a tertiary care setting who underwent endoscopic intervention was studied. Response to treatment was evaluated by improvement in dysphagia score on a scale of 0-4 and weight gain. Results: 99 subjects (53 males) were included. Mean age was 48.6±17.2 years. Dysphagia for solids was present in 48%, for liquids in 3% and for both in 49% patients. Significant weight loss (>10% body weight) occurred in 35 (35.3%) patients. Achalasia was diagnosed in 49.5%, peptic stricture in 30.4%, post sclerotherapy stricture in 12.1%, corrosive injury in 4%, post-operative stricture in 4%. In comparative analysis of achalasia and inflammatory groups, good response to dysphagia was seen in 40/49 (82%) and 22/50 (44%) respectively p < 0.001. Weight gain was 35/49 (72%) and 22/50 (44%) p <0.001 respectively. Significantly, more endoscopic sessions were required in inflammatory group compare to achalasia; 2.2 and 1.1 respectively; p <0.001 and 16% complications rate in inflammatory group comparing to no complications in achalasia. Conclusions: Dysphagia and weight loss were common presentations in non-malignant esophageal diseases. Therapeutic intervention in inflammatory group was associated with high complication than the achalasia group. Key words: outcome of non-malignant esophageal diseases, Benign esophageal lesions, Achalasia, esophageal strictures.